Efficacy and safety of percutaneous microwave ablation for hepatocellular carcinomas <4 cm in difficult location - Mukund, Amar (Br J Radiol, 2020)
OBJECTIVE: Tumor location is a critical factor for determining technical success and local recurrence following percutaneous ablation of hepatocellular carcinomas (HCC). The purpose of this retrospective study was to evaluate the safety and outcome measures of percutaneous microwave ablation (pMWA) for HCCs <4 cm in difficult locations. METHODS: Retrospective review included 81 patients who underwent pMWA for HCCs <4 cm. Fourty-three patients (30 males and 13 females; mean age, 61 years) with 53 HCCs located near the diaphragm, heart, gallbladder, kidney, gastrointestinal tract, large vessel and exophytic location were included under difficult location group. Thirty-eight patients (29 males and nine females; mean age, 60 years) with 48 HCCs in other locations were included under control group. Baseline demographics were recorded. Technical efficacy, local tumor progression (LTP), and complication rates were evaluated. RESULTS: Mean follow-up period was 3.4 months (range 1–7). There was no major complication in both the groups; two patients had a mild perihepatic hemorrhage in the difficult location group which was managed conservatively. There was no difference between the groups in the overall technical efficacy rate (84.9% vs 91.7%, p = 0.294), LTP rate (4.4% vs 2.2%. p = 0.57) or complication rate (4.6% vs 0%, p = 0.177). CONCLUSION: Our data suggest that there is no significant difference in technical efficacy, LTP or complication rates for MWA in both difficult and normal locations. ADVANCES IN KNOWLEDGE: With proper patient selection, pre-procedural planning and appropriate technique, pMWA is feasible, safe, and effective for small HCCs in difficult location with an acceptable range of complications.